Ceramics of Ancient America : Multidisciplinary Approaches - Minich, Johanna; Arnold, Dean E., 1942-; Park Huntington, Yumi (University Press of Florida, 2018)
This edited volume analyzes ceramics specifically from ancient America to add new layers to our understanding by emphasizing new perspectives and a multidisciplinary approach from the fields of archaeology, art history, and anthropology. This volume will help students and scholars alike better understand and appreciate ceramics as one of the vital forms of communication within small social units, and across cultural and political boundaries.